Global christianity ante portas - Jurekovič, Igor (Annales. Series historia et sociologia, 2024)
Christianity’s centre of gravity has moved south, giving rise to the phenomenon of Global Christianity. This has in turn enabled the phenomenon of the reverse mission. Largely a missionary concept, reverse mission loosely refers to the conscious attempts by Global South churches to re-evangelise Europe. In any event, reverse missions have not been successful in converting non-immigrant Europeans. This paper analyses and reflects upon missionary and theological writings on these failures. Analysing the clashing Christianities, we pinpoint the religious body as an overlooked dimension of reverse mission failures. It is thus shown that the clash of Christianities reveals the clash of culturally specific conceptions of religion.
Keywords: globalno krščanstvo; karizmatično krščanstvo; migracije; povratni misijon; religija; sociologija religije; telo